Phase portraits of some polynomial differential systems with maximal multiplicity of the line at the infinity - Vadim Repeșco (Acta et Commentationes: Ştiinţe Exacte şi ale Naturii)
The present study delves into the investigation of phase portraits of polynomial differential systems, which are systems of differential equations of the form $\frac{dx}{dt} = P(x,y), \frac{dy}{dt} = Q(x,y)$, where $x$ and $y$ are the dependent variables and $t$ is the independent variable. The functions $P(x,y)$ and $Q(x,y)$ are polynomials in $x$ and $y$. The main objective of this research is to obtain the phase portraits of polynomial differential systems of degree $n\in \{ 3, 4, 5\}$ and having an invariant straight line at the infinity of maximal multiplicity.